Inventory of Potential Attraction of Sungai Langka & Wiyono Village as Cocoa Tourism Village Program at Pesawaran Regency - Cahyo, Enggar Dwi; Ridwansyah, Eksa; Siregar, Damara Saputra (Penerbit Goodwood, 2022)
Purpose: This article aims to to determine the potential and perceptions of villagers towards tourism objects as the result for become Cocoa Village at Pesawaran Regency. Method: This research descriptive qualitative with data collection techniques by distributing questionnaires, interviews, and observations at the locus area. To see the public's perception of the tourism aspect in Sungai Langka Village and Wiyono Village, this study used the IPA (Importance Performance Analysis) technique. Results: The results show that the Sungai Langka & Wiyono Village has a complete tourism object like natural tourism attraction, cultural tourism attraction and artificial tourism attraction. There are adequate primary and secondary facilities, as well as accessibility to the object. Local people perceptions of the attractiveness of tourist objects in Sungai Langka & Wiyono are very good in terms of natural scenery, cultural wealth, artificial tourism potentials, and accessibility. Limitation: This research was only conducted at used only revolves around the building and construction that in 2018 until 2020, firms from the subsector should be registered on the Indonesia Stock Exchange Contributions: This exploration has contributed to the enrichment of aspects of the management accounting literature, especially in construction and building sub-sector companies.